Effectiveness of farm waste management in Penang / Asrul Azali Kamaruddin - Kamaruddin, Asrul Azali (Faculty of Civil Engineering, 2006)
This project is proposed to meet the direct request from the Prime Minister of Malaysia who encourages research activities based on BioTechnology and Environmental protection in Malaysia. The Malaysian government has placed the sustainable, renewable and biotechnology based research and development as the highest priority in its National Research and Development Strategy. Currently, farm wastes such as swine, poultry manure and cattle dungs are directly disposed/discharged in to the open channels and river systems. These problems are clearly evident among the small scale farmers who are cannot affort to have a sophisticated and costly waste treatment plants. It causes an alarming rate of enviromental pollution, expecially water pollution. Thus, a new methodology for the treatment farm waste namely ‘plug-flow anaerobic digester’ is proposed. At the same time this system also designed to produce Bio-gas for domestic use. The research conducted successfully demonstrate the use of beef dung to be used in the anaerobic digester to yield methane gas. The system suggest if implemented at the field scale may help the farmers, reduce pollution and even more give profit to farmers. This project demonstrate the bridge of bioengineering knowledge that it can be apply in various sector and will be the pioneer idea to others future or present civil engineers.